THE INFLUENCE OF pH AND FLOTATION TIME TO Pb RECOVERY IN GALENA ORE PROCESSING WITH SELECTIVE FLOTATION ON LABORATORY SCALE - MALIK (NIM : 121 05 065); Pembimbing : Dr. Ir. Ismi Handayani, MT, SYABARUDDIN
Flotation is one of concentration processes that utilises the difference in surface properties of the valuable minerals and the unwanted gangue minerals for separation process. Because of the selective process, this flotation process is frequently applied to separate sulphide minerals in complex ore that could contain galena, sphalerite, chalcopyrite, and gangue minerals. There are variables that persuade the flotation process : ore liberation, ore grain size, flotation reagents usage, pulp solid percentage, conditioning time, flotation time , and pH. The galena samples of this selective flotation research come from Nanggung, Bogor.. The flotation parameters that are variated in this research are pH (pH tested= pH 7, pH 8, pH 9, dan pH 10) and flotation time (flotation time tested = 1, 4, 7, 10 minutes) on each grades. The research steps are divided into 3 major process : preparation step, flotation step, and content analysis of flotation result step. The purpose of this research is to find the best condition in pH and flotation time in selective flotation process on laboratory scale with the best Pb recovery. The result of the flotation research with pH variation shows that the highest Pb recovery percentage of low-content galena ore (37,79 %), mid-content galena ore (42,52 %), and high-content galena ore (51,87 %) are in 1st concentrate on each grades in pH 9 condition. The result of the flotation research with flotation time variation shows that the highest Pb recovery percentage of low-content galena ore (45,98 %), middle-content galena ore (52,29 %), and high-content galena ore (58,96%) are in 1st concentrate on each samples in 10 minutes flotation time.